Fractures involving bony orbit: A comprehensive review of relevant clinical anatomy - Sanjib Kumar Ghosh; Ravi Kant Narayan (Elsevier, 2021)
Introduction: Orbital fractures are commonly reported following injury to maxillofacial region. Management of these fractures often poses a challenge due to potential involvement of a number of anatomical structures. Hence this study was attempted to collate the anatomical details relevant to clinical presentation of orbital fracture as available in published literature from clinical domain. Materials & methods: A literature search of relevant, peer-reviewed, published articles was undertaken from indexed databases (Medline & Pubmed, Scopus, Embase, CINAHL Plus, Web of Science and Google Scholar). Results: Orbital fractures are broadly classified as isolated orbital fractures (blowout fracture) and combined orbital fractures. Blowout fractures commonly involve the floor of orbit and may/may not be associated with fracture of medial wall or zygomatic component of lateral wall of orbit. Combined orbital fractures involve orbital rim (anterior third) along with orbital walls (middle third) and may even involve the posterior third of bony orbit. Both types of orbital fractures are associated with the risk of injury to related anatomical structures. The clinical presentation of these fractures closely reflects the injuries caused to anatomical structures associated with orbital regions damaged due to trauma. Conclusion: The contents of this study may be useful for relevant surgical specialities in clinical assessment and management of orbital fractures.